McGraw-Hill's national electrical code handbook - McPartland, Brian J. (McGraw-Hill NEC series, 1999)
Every three years since 1932, electricians have used this Handbook to clarify the National Electrical Code. New to this edition are an article covering requirements for multi-building facilities and descriptions of additional requirements for the proper use of a wide range of equipment.